Depression as a Risk Factor for Dementia: Pathophysiology and Preclinical Study Models; [la Depresión Como Factor de Riesgo de la Demencia: Fisiopatología y Modelos Preclínicos de Estudio] - Wong-Guerra, M (Sociedad Espanola de Psiquiatria Biologica (SEPB), 2024)
The increase in life expectancy has led to a rise in the incidence of chronic diseases, such as dementia. Treating the risk factors of dementia, such as depression, could help reduce its occurrence. However, antidepressant treatment has not proven effective in managing this symptom, thereby increasing the risk of dementia in the future. It is essential to investigate the causes and treatment of depression, and in this regard, the use of animal models is of great significance. This study aims to analyze the evidence supporting the relationship between depression and the risk of developing dementia, while also providing an update on the most relevant preclinical models for studying depression in rodents. © 2023
Keywords: Animal models; Cognitive dysfunction; Dementia; Depression; Preclinical models; Risk factor